The Influence of Company Size, Sales Growth and Leverage on Financial Distress: Empirical Study on Technology Sector Companies Listed on the Indonesia Stock Exchange for the Period 2021-2023 - Napitupulu, Ruth Sri Indah; Wiralestari, Wiralestari; Erwati, Misni (International Journal of Multidisciplinary Approach Research and Science, 2025)
This research explores the relationship between financial vulnerability and three key corporate metrics, organizational magnitude, revenue expansion, and debt ratio, specifically examining technology enterprises registered on the Indonesian Securities Market from 2021 through 2023. The investigation treats organizational magnitude, revenue expansion, and debt ratio as predictor variables, with financial vulnerability serving as the outcome measure. The researchers employed a numbers-based analytical framework. The target population encompassed technology industry corporations listed on the ISM throughout the three-year period under scrutiny. Employing criterion-based selection methods, researchers identified 20 appropriate corporations for comprehensive evaluation. Statistical calculations utilized multiple correlation techniques through IBM's analytical software platform (SPSS v27). All numerical information was sourced secondarily via the Indonesian Securities Market's digital repository. The analytical outcomes reveal that organizational magnitude, revenue expansion, and debt ratio collectively demonstrate statistically meaningful correlation with financial vulnerability. Moreover, each individual factor, organizational magnitude, revenue expansion, and debt ratio, exhibits its own distinctive relationship with corporate financial vulnerability.